Complexity of Love in Wuthering Heights and Tenggelamnya Kapal Van Der Wijck - Satria, Sistiadinita Abang; Oktavianda, Melti (Lexicon, 2025)
This study explores the theme of doomed love as depicted in Buya Hamka’s Tenggelamnya Kapal Van der Wijck (1938) and Emily Brontë’s Wuthering Heights (1847), examining the profound social barriers that doomed these relationships. It particularly focuses on the characters Zainuddin and Heathcliff, who are both rejected by their societies and lovers due to insurmountable social inequalities, a rejection that culminates in the tragic deaths of their beloveds. The aim of this paper is to dissect how intrinsic narrative elements and socio- cultural contexts collectively shape the central themes of love and societal rejection in these works. The approach used in this study is Genetic Structuralism by Lucien Goldmann (1980), a literary theory that combines structural analysis with socio-cultural context. This approach argues that a literary work should be understood as a product of both its internal structure and the socio-historical conditions in which it was created. The dialectical method is used to analyze and compare literary works by examining the interaction between intrinsic elements of the texts (structures) and their socio-historical contexts (worldviews). Applying this method to compare Tenggelamnya Kapal Van der Wijckand Wuthering Heights involves tracing the internal structures of each text, including characters, narrators, irony, and worldviews, and the external socio- historical realities shaping these structures, such as colonialism and traditionalism in Indonesia for Hamka, and industrialization and social stratification in England for Brontë. The findings show how in both works, love is portrayed as a complex and often obstructed idea, shaped by cultural and social barriers of their eras and worldviews of their authors. This idea simultaneously reflect their unique cultural contexts and engage with universal human questions about morality, love and society.